Wee warriors and playtime patriots children's military regalia, Civil War through the Vietnam era - Griffith, Nanci 1953-2021 (Schiffer Publ., 2001)
Handmade and commercially made replica uniforms, equipage and toys dating from 1860-1976, plus a collection of photographs featuring children in military dress from countries around the world. Includes a detailed buying guide (p. [209]-219) of images, swords, drums, headgear, uniforms and miscellaneous (insignia, boots, etc.)